Spotted Pod Borer A potential threat to short duration pigeonpea - Mohapatra, S D; Chattopadhyay, C (Indian Farming, 2015)
In recent years the spotted pod borer, Maruca vitrata (Geyer) has emerged as a major pest in short duration pigeonpea growing areas of India. Because of the high humidity and moderate temperature during flowering, this pest has emerged as a destructive one on short duration pigeonpea varieties having clustering type of branching habit. Application of rynaxypyr 20EC @ 0.4ml or profenphos 50EC @ 2.0 ml or methomyl 40SP @ 1.0 g in combination with DDVP @ 0.5 ml/l of water or garlic bulb extract @ 1% + rynaxypyr 20EC @ 0.4ml/l of water at the time of flowering and podding saves the crop from Maruca infestation.